The truth will set you free, but first it will piss you off : thoughts on life, love, and rebellion - Steinem, Gloria (Random House, 2019)
"For decades -- and especially now in these times of crisis -- people around the world have found guidance, humor, and unity in Gloria Steinem's gift for creating quotes that inspire action and create hope. From her early days as a journalist and feminist activist, up to today, Steinem's words have helped generations to empower themselves and work together. Gloria sees quotes as 'the poetry of everyday life,' so she also has included a few favorites from friends, including Bell Hooks, Flo Kennedy, Michelle Obama, and more, in this anthology of quotes that will make you want to laugh, march, and create some of your own. At the end of the book, there is a special space for each reader to add their own quotes and others they've found. Covering topics from relationships ('Many are looking for the right person. Too few are looking to be the right person.') to patriarchy ('Men are liked better when they win. Women are liked better when they lose. This is how patriarchy is enforced every day.') and activism ('Change, like a tree, grows from the bottom up.'), plus an introduction and essays by Steinem, this is the definitive collection of her words on many of the topics that matter most today. The Truth Will Set You Free, But First It Will Piss You Off! is both timeless and timely. It is a gift of hope from Gloria to readers, that they will want to share with friends"--